The economic burden of Chagas disease: A systematic review. - Mônica Viegas Andrade; Kenya Valéria Micaela de Souza Noronha; Aline de Souza; André Soares Motta-Santos; Paulo Estevão Franco Braga; Henrique Bracarense; Maria Carolina Corrêa de Miranda; Bruno Ramos Nascimento; Israel Molina; Francisco Rogerlândio Martins-Melo; Pablo Perel; Yvonne Geissbühler; et al. (Public Library of Science (PLoS), 2023)
Background Chagas disease (CD) is a neglected disease affecting millions worldwide, yet little is known about its economic burden. This systematic review is part of RAISE project, a broader study that aims to estimate the global prevalence, mortality, and health and economic burden attributable to chronic CD and Chronic Chagas cardiomyopathy. The objective of this study was to assess the main costs associated with the treatment of CD in both endemic and non-endemic countries. Methods An electronic search of the Medline, Lilacs, and Embase databases was conducted until 31st, 2022, to identify and select economic studies that evaluated treatment costs of CD. No restrictions on place or language were made. Complete or partial economic analyses were included. Results Fifteen studies were included, with two-thirds referring to endemic countries. The most commonly investigated cost components were inpatient care, exams, surgeries, consultation, drugs, and pacemakers. However, significant heterogeneity in the estimation methods and presentation of data was observed, highlighting the absence of standardization in the measurement methods and cost components. The most common component analyzed using the same metric was hospitalization. The mean annual hospital cost per patient ranges from $25.47 purchasing power parity US dollars (PPP-USD) to $18,823.74 PPP-USD, and the median value was $324.44 PPP-USD. The lifetime hospital cost per patient varies from $209,44 PPP-USD for general care to $14,351.68 PPP-USD for patients with heart failure. Discussion Despite the limitations of the included studies, this study is the first systematic review of the costs of CD treatment. The findings underscore the importance of standardizing the measurement methods and cost components for estimating the economic burden of CD and improving the comparability of cost components magnitude and cost composition analysis. Finally, assessing the economic burden is essential for public policies designed to eliminate CD, given the continued neglect of this disease.